Ameliorative Effects of Myrtus Communis L. Extract Involving the Inhibition of Oxidative Stress on High Fat Diet-Induced Testis Damage in Rats - Coskunlu, Busra; Koroglu, M. Kutay; Hersek, Irem; Ertas, Busra; Sen, Ali; Sener, Goksel; Ercan, Feriha (Taylor & Francis Ltd, 2024)
The possible protective effects of Myrtus communis L. (MC) extract on a high fat diet (HFD)-induced testicular injury in a rat model were investigated using histological and biochemical methods. Wistar albino rats were divided into three groups: a standard diet control group; a HFD group; and an HFD+MC group. The HFD and HFD+MC groups were fed with a HFD for 16 weeks. MC extract (100 mg/kg) was given orally five days a week to the rats in the HFD+MC group during the last four weeks of the experiment. Leptin, triglyceride, high-density lipoproteins, cholesterol, estrogen, testosterone, LH and FSH were analyzed in blood serum. Sperm parameters were evaluated from the epididymis. Testicular morphology, proliferative, apoptotic and NADPH oxidase-2 (NOX2)-positive cells were evaluated histologically. Testicular oxidative stress parameters were analyzed biochemically. In the HFD group, lipid and hormone profiles were changed, abnormal spermatozoa, degenerated seminiferous tubules with apoptotic and NOX2-positive cells were increased in number, and sperm motility and germinal proliferative cells decreased compared to the control group. Moreover, testicular malondialdehyde, 8-hydroxy-2-deoxyguanosine and myeloperoxidase levels increased, whereas glutathione and superoxide dismutase levels decreased in the HFD group compared to the control group. All these histological and biochemical features were ameliorated by MC treatment of HFD-fed rats. In conclusion, HFD caused alterations in sperm parameters and testicular morphology by increasing oxidative damage and apoptosis. MC extract may have potential protective effects by inhibiting oxidative damage.
Koroglu, Kutay/0000-0002-5384-4472; Sener, Goksel/0000-0001-7444-6193; ERTAS, BUSRA/0000-0001-8374-1098; Sen, Ali/0000-0002-2144-5741; Ercan, Feriha/0000-0003-2339-5669
Keywords: Apoptosis; High Fat Diet; Myrtus Communis Extract; Oxidative Stress; Testis